2020
DOI: 10.1162/jocn_a_01556
|View full text |Cite
|
Sign up to set email alerts
|

Zooming In and Out on One's Life: Autobiographical Representations at Multiple Time Scales

Abstract: The ability to decouple from the present environment and explore other times is a central feature of the human mind. Research in cognitive psychology and neuroscience has shown that the personal past and future is represented at multiple timescales and levels of resolution, from broad lifetime periods that span years to short-time slices of experience that span seconds. Here, I review this evidence and propose a theoretical framework for understanding mental time travel as the capacity to flexibly navigate hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 208 publications
(310 reference statements)
3
61
0
3
Order By: Relevance
“…When examining the unique contribution of these factors, we found that belief in future occurrence was predicted by both the quality of future thoughts (the vividness of mental imagery and ease of imagination) and their integration with autobiographical knowledge (personal importance and plans). These findings add to growing evidence that autobiographical knowledge plays a central role in episodic future thinking (D'Argembeau, in press; D'Argembeau & Demblon, 2012; D'Argembeau & Mathy, 2011).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…When examining the unique contribution of these factors, we found that belief in future occurrence was predicted by both the quality of future thoughts (the vividness of mental imagery and ease of imagination) and their integration with autobiographical knowledge (personal importance and plans). These findings add to growing evidence that autobiographical knowledge plays a central role in episodic future thinking (D'Argembeau, in press; D'Argembeau & Demblon, 2012; D'Argembeau & Mathy, 2011).…”
Section: Discussionsupporting
confidence: 71%
“…While belief in future occurrence can be influenced by multiple factors, it is largely determined by the congruence of imagined events with general knowledge about the self and one's life—events feel real because they are planned or because they are consistent with our personal life circumstances (D'Argembeau, in press; Ernst et al, 2019; Ernst & D'Argembeau, 2017; Scoboria et al, 2020). To illustrate this, consider the difference between imagining that you will be relaxing on the beach next weekend and imagining that you will be at the office working on a paper.…”
Section: Discussionmentioning
confidence: 99%
“…Building on similarities in subdomains of imagination, we suggest that there are two imagination-driven subsystems within the default network: one that supports our ability to evoke an internal mind’s eye and the other an internal mind’s mind (Fig. 1; Raffaelli et al, 2020; for related views, see D’Argembeau, 2020; Irish, 2020; Sheldon et al, 2019).…”
Section: Mapping the Cognitive And Neural Landscape Of The Imaginativmentioning
confidence: 78%
“…Supporting our ability to retrieve and relate together items, objects, spatial locations, and other concrete forms of knowledge, the mind’s eye also affords us the flexibility to construct new ideas and mental scenarios, such as envisioning what might lie ahead, dreaming vividly, or thinking creatively. Drawing on evidence from a range of imagination tasks, we link the mind’s eye with a default-network subsystem involving the medial temporal lobe and its cortical connections, including midline parietal regions spanning the retrosplenial cortex and parts of the posterior cingulate cortex, a lateral parietal region called the inferior parietal lobe, and other cortical and subcortical regions (Andrews-Hanna et al, 2014; D’Argembeau, 2020; Sheldon et al, 2019).…”
Section: Mapping the Cognitive And Neural Landscape Of The Imaginativmentioning
confidence: 99%
“…Examining the status of memories encoded prior to disease onset provides an important window into the nature and severity of memory impairment in neurological disorders. Here, we focus on autobiographical memory; the recollection of personally-relevant experiences replete with rich sensory-perceptual, emotional, and semantic information (Conway, 2001; Irish and Piguet, 2013; D’Argembeau, 2020). Autobiographical memory is a particularly fruitful aspect of memory to explore given the availability of well-validated interview techniques that have been reliably used in neurodegenerative populations (see, for example McKinnon et al ., 2006; McKinnon et al ., 2008; Irish et al ., 2011a; Hsieh et al ., 2016; Ahmed et al ., 2018; Irish et al ., 2018; Carmichael et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%